Pretended Personality and Its Relationship to Self-Assertion Among a Sample of Adolescents (Journal of Hama University, 2020)
The aim of the present research is to identify the nature of the relationship between Pretended personality and self-affirmation among a sample of adolescents of the first year students at Damascus University, by sex variable (male, female).The Pretended personality and the self - affirmation of Rathus (1978) were used. The total sample size was 300)) adolescents.The study reached the following results:1. A high level of artificial character in the research sample.2. There is a statistically significant negative correlation between the Pretended personality and self-affirmation among the research sample.3. There are statistically significant differences between the mean scores of the research sample on the scale of the Pretended personality according to the sex variable and for the benefit of females.4. There are no statistically significant differences between the mean scores of the research sample on the self-affirmation scale according to the sex variable (male, female).